Thermogravimetry Analysis of Electrochemically Synthesized Polypyrrole Conducting Polymer Films - Ansari Khalkhali, Reza; B. Keivani, Mohammad (Asian Journal of Chemistry, 2016)
Free standing films of polypyrrole were prepared in the presence of different organic dopants at room temperature electrochemically (galvanostaic method). Thermal stability of polypyrrole films was then investigated using thermogravimetry analysis technique. On investigation of thermal stability of polypyrrole films of by using thermogravimetry analysis, it was found that in all cases the polymer (PP+/C–) decomposed at temperatures below the decomposition temperature of their dopant or counterions. It was found that thermal stability of polypyrrole conducting polymers is affected by the nature of its dopant anion which is employed during electropolymerization. Electropolymerization of polypyrrole in the presence of benzene sulfonate dopants with small and non-nucleophilic substitutions under suitable synthesis conditions produces more thermally stable polymer films.